Water‐Soluble, Spin‐Cast‐Based Crystalline Poly(Methacrylic Acid) Film as a Reversible Li‐Ion Battery Anode - Minjin Son; Hyeongjun Kim; Minju Lee; Jonggeon Na; Sang Kyu Kwak; Seok Ju Kang (Small Structures)
Poly(methyl methacrylate) (PMMA) polymer anodes are proposed as potential reversible anode materials for lithium‐ion batteries (LIBs) owing to their simple thin‐film formation process and cost‐effectiveness. Nevertheless, challenges such as the use of toxic aprotic solvents and the irreversible consumption of Li ions during the initial cycle need to be addressed to improve their performance. Herein, a water‐soluble poly(methacrylic acid) (PMAA) polymer processed using a simple spin‐casting method as a reversible LIB anode is presented. Unlike the PMMA anode, the conjugated carbonyl groups of the crystalline PMAA polymer readily form a chain backbone during ex situ thermal annealing, demonstrating a reversible capacity. The mechanism underlying the superior electrochemical characteristics of the PMAA anode is revealed using grazing incidence X‐ray diffraction and theoretical calculations. In particular, the highly crystalline cyclic anhydride PMAA polymer induced by thermal annealing shows enhanced interactions between Li ions and CO groups during operation, resulting in improved electrochemical properties. The resulting crystalline cyclic anhydride PMAA anode achieves a capacity of ≈427.7 mAh g−1 and retains a reversible specific capacity of 156 mAh g−1 after 500 cycles, indicating that it is a promising polymeric anode for next‐generation LIBs.